Performance evaluation of the sysmex XN-1000V automated hematology analyzer in marine fish species: Gilthead seabream (Sparus aurata) - Montse Mesalles; Josep Pastor; Emmanuel Serrano; Rafaela Cuenca; Lluís Tort; Mariana Teles (PLoS ONE, 2026)
Hematological analyses are widely used to assess the health and physiological status of animals, including fish. Automated hematology analyzers enable rapid and reproducible hematological measurements; however, their application in fish requires species-specific analytical validation due to the presence of nucleated blood cells. This study evaluated the analytical performance of the Sysmex XN-1000V hematology analyzer operated under avian settings (PLT-F channel), in juvenile gilthead seabream ( Sparus aurata ), one of the cornerstone species of Mediterranean marine aquaculture. Analytical validation included assessment of precision, linearity, carryover, and sample stability. Results were compared with manual reference methods (hemocytometer counts and blood smear-based estimates). In addition, the influence of two anticoagulants (lithium heparin and K₂EDTA) was examined, and the analyzer’s ability to detect lipopolysaccharide (LPS)-induced changes in non-erythroid cell population was evaluated. The analyzer showed good precision for most parameters (CV < 5%), although higher variability was observed for granulocyte percentage. Linearity was excellent (R 2 ≥ 0.98), and carryover remained below 1% for all variables. Sample stability was significantly better at 4 °C than at room temperature (25 °C), supporting refrigerated storage for up to 24 hours prior to analysis. Comparison with manual reference methods revealed strong correlations and agreement for red blood cell counts and hematocrit, whereas discrepancies were identified in non-erythroid cells differentials. Among anticoagulants, lithium heparin yielded more consistent and reliable results than K₂EDTA. Erythrocyte-related parameters showed the highest analytical reliability, whereas the leucocyte differentiation within the non-erythroid fraction required complementary microscopic evaluation, particularly when assessing LPS-induced inflammatory changes. Overall, the Sysmex XN-1000V demonstrated suitable analytical performance for routine hematological assessment in gilthead seabream when operated under avian settings. These findings support its application in aquaculture health monitoring programs, provided that appropriate anticoagulants are used, samples are promptly processed or refrigerated, and automated results are complemented by microscopic review when leukocyte counts are suspected.